5x-6x-3=-5

Simple and best practice solution for 5x-6x-3=-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-6x-3=-5 equation:


Simplifying
5x + -6x + -3 = -5

Reorder the terms:
-3 + 5x + -6x = -5

Combine like terms: 5x + -6x = -1x
-3 + -1x = -5

Solving
-3 + -1x = -5

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + -1x = -5 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -5 + 3
-1x = -5 + 3

Combine like terms: -5 + 3 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 6+4(3-2n)=-4n+14 | | 1/6=1.5x | | 8y=-3x+4 | | 5b-2=18 | | 52x^3-122x^2+66x=0 | | -2n=6-2n | | -8x+8+5x=2 | | -3x+3=2 | | 6x+4.50y=45 | | 20.4/3.4= | | 2x/9-9/3=8-3x | | 6(x-2)+5x=9x-2(4-3) | | 9x+4=64 | | -7x+2y=70 | | .66x-6+3=4x-4 | | 4.5*4.4= | | 2x^2=2048 | | 3x(5x-54)= | | -5/9*(-4) | | 17d+104=998 | | 3s+144=531 | | 5(2x-2)=6x+9 | | t-671/11=19 | | 12=336/f | | -39+7x=4x-6(x+8) | | 103-8m=31 | | 36+3h=84 | | 5x-12=2x+14 | | 9x+8y+8z=40 | | -7x(-6*0)=-15 | | 377/j=13 | | ex^2=0 |

Equations solver categories